Santri Mengajar: The Amaliyah Tadris Model in Shaping the Spirit and Teaching Skills at Nurul Hakim Islamic Boarding School, West Lombok - Baiq Ninda Auliya; Muhammad Muhammad; Emawati Emawati (Fitrah, 2026)
This study aims to analyze the "Santri Mengajar" (Students Teach) model through the implementation of the Amaliyah Tadris program in developing the pedagogical and professional competencies of students (santri) at the Nurul Hakim Islamic Boarding School (Pesantren) in Kediri, West Lombok. Using a qualitative descriptive approach with a case study method, the researcher acted as the primary instrument. Primary data were obtained through non-participatory observation, documentation of learning plans, and semi-structured interviews with the boarding school leadership, teachers (asatidz), supervisors (musyrif/musyrifah), and students. Data analysis was conducted interactively, encompassing data condensation, data display, and conclusion drawing, with validity checks performed through prolonged observation and triangulation. The results of the study show that: First, the Amaliyah Tadris program is implemented through a structured systemic cycle that integrates the curricula of the Ministry of Religious Affairs, Medina, and Gontor. This includes the stages of lesson plan preparation (I’dad), teaching practice (Tadris), and critical evaluation through a Naqd (critique) session based on the values of al-‘adl (justice), ash-shihah (truth), at-ta’aawun (cooperation), and al-ifadah (usefulness). Second, this program simultaneously succeeds in developing the students' pedagogical competence by forming the profile of Mudarris al-Mahir (skilled teacher) and professional competence by fostering Ruh al-Mudarris (the spirit of an educator). Nevertheless, a critical-reflective analysis indicates challenges in the form of procedural rigidity and tight clinical supervision patterns, which potentially limit the instructional creativity space of the practicing students.